The Cretaceous ammonite Hemiptychoceras Spath in Antarctica - Medina, Francisco Alberto; Scasso, Roberto Adrian
The occurrence of the heteromorph ammonite genus Hemiptychoceras Spath is reported for the first time from Antarctica. Previously described from the Upper Albian-Lower Cenomanian of Europe, India, Madagascar, Zululand (South Africa) and Blake Plateau (northern Florida, in the western Atlantic), the new material is identified with the species Hemiptychoceras tropicum (koSSmat), hitherto known only from India. It provides an important new biostratigraphical datum. Hemiptychoceras tropicum has been collected from a single level at each of two localities where the Whisky Bay Formation (Gustav Group) crops out. It is associated with Mariella sp., Anagaudryceras sacya (ForbeS) and the bivalve Actinoceramus cf. concentricus (parkinSon). On the basis of this assemblage and the underlying and overlying mollusc faunas an early Cenomanian age is suggested. Fil: Medina, Francisco Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Geológicas. Área de Sedimentología; Argentina Fil: Scasso, Roberto Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Geológicas. Área de Sedimentología; Argentina